2023
DOI: 10.3389/fphar.2023.1108992
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic drugs in combination with seaweed fucoidan: A mechanistic in vitro and in vivo study exploring the VEGF receptor and its downstream signaling molecules in hepatic cancer

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers reported worldwide with poor morbidity and high mortality rates. HCC is a very vascular solid tumour as angiogenesis is not only a key driver for tumour progression but also an exciting therapeutic target. Our research investigated the use of fucoidan, a sulfated polysaccharide readily abundant in edible seaweeds commonly consumed in Asian diet due to their extensive health benefits. Fucoidan was reported to possess a strong anti-cancer activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These results suggest their potential use in the treatment of angiogenesis-related malignancies [203] (Table 1). [192,195,196] Fucoidan Edible brown seaweeds HCC; Huh-7 cells VEGF-A gene downregulation [199,200] Carnosol and Carnosic acid…”
Section: Carnosol and Carnosic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest their potential use in the treatment of angiogenesis-related malignancies [203] (Table 1). [192,195,196] Fucoidan Edible brown seaweeds HCC; Huh-7 cells VEGF-A gene downregulation [199,200] Carnosol and Carnosic acid…”
Section: Carnosol and Carnosic Acidmentioning
confidence: 99%
“…Fucoidan was also evaluated for its activity in combination with sorafenib and bevacizumab in HCC. In vitro, on Huh-7 cells, fucoidan showed a potent synergistic effect with anti-angiogenic drugs and significantly reduced the HCC cell line viability in a dose-dependent manner via the inhibition of the pro-angiogenic PI3K/AKT/mTOR and KRAS/BRAF/MAPK pathways [ 200 ] ( Table 1 ).…”
Section: Phytochemicals To Counteract the Stages Of Liver Disease Via...mentioning
confidence: 99%
“…Unfortunately, the uncharacterized source and structure of the fucoidan do not allow us to draw a conclusion with any certainty. The antiangiogenic activity of fucoidan from Laminaria Japonica was also investigated in a diethyl nitrosamine (DEN)-induced hepatocarcinoma rat model in combination with the two anti-angiogenic drugs avastin and sorafenib [ 58 ]. Fucoidan alone did not significantly decrease the expression of AFP (alpha fetoprotein), a key marker of tumor burden and prognosis, VEGF or VEGFR, although a reduction in their levels was observed in combination with the anti-angiogenic drugs [ 58 ].…”
Section: Antiangiogenic and Antimigratory Effects Of Fucoidansmentioning
confidence: 99%
“…Additionally, the proliferation and cell migration of human umbilical vein endothelial cells (HUVECs) were inhibited via the suppression of the phosphorylation of VEGFR2, which halted signal transduction [109]. Abdollah et al reported that the attenuation effect of fucoidan against Avastin in HCC cells was stimulated by the inhibition of VEGF expression and secretion as well as the modulation of other signaling pathways, including PI3K/AKT/mTOR and the RAS/RAF/MAPK [110]. Elsewhere, the antiangiogenic effect of fucoidan in prostate cancer cells was mediated via the inhibition of the VEGF coupled with a reduced phosphorylation of the JAK-STAT3 pathway [111].…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%